Prevalence and Associated Features of Anxiety Disorder Comorbidity in Bipolar Disorder: A Meta-Analysis and Meta-Regression Study - Yapici Eser, Hale; Kacar, Anil S.; Kilciksiz, Can M.; Yalçinay-Inan, Merve; Ongur, Dost (Frontiers in Psychiatry, 2018)
Objective: Bipolar disorder is highly comorbid with anxiety disorders, however current and lifetime comorbidity patterns of each anxiety disorder and their associated features are not well studied. Here, we aimed to conduct a meta-analysis and meta-regression study of current evidence. Method: We searched PubMed to access relevant articles published until September 2015, using the keywords ‘Bipolar disorder’ or ‘Affective Psychosis’ or ‘manic depressive’ separately with ‘generalized anxiety’, ‘panic disorder’, ‘social phobia’, ‘obsessive compulsive’ and ‘anxiety’. Variables for associated features and prevalence of anxiety disorders were carefully extracted. Results: Lifetime any anxiety disorder comorbidity in BD was 40.5 %; panic disorder (PD) 18.1 %, generalized anxiety disorder (GAD) 13.3 %, social anxiety disorder (SAD) 13.5 % and obsessive compulsive disorder (OCD) 9.7 %. Current any anxiety disorder comorbidity in BD is 38.2 %; GAD is 15.2 %, PD 13.3 %, SAD 11.7 % and OCD 9.9%. When studies reporting data about comorbidities in BDI or BDII were analyzed separately, lifetime any anxiety disorder comorbidity in BDI and BDII were 38 % and 34 %, PD was 15 % and 15 %, GAD was 14 % and 16.6 %, SAD was 8 % and 13 %, OCD was 8 % and 10 %, respectively. Current any DSM anxiety disorder comorbidity in BDI or BDII were 31 % and 37 %, PD was 9 % and 13 %, GAD was 8 % and 12 %, SAD was 7 % and 11 %, and OCD was 8 % and 7 %, respectively. The percentage of manic patients and age of onset of BD tended to have a significant impact on anxiety disorders. Percentage of BD I patients significantly decreased the prevalence of panic disorder and social anxiety disorder. A higher rate of substance use disorder was associated with greater BD – SAD comorbidity. History of psychotic features significantly affected current PD and GAD. Conclusions: Anxiety disorder comorbidity is high in BD with somewhat lower rates in BDI vs BDII. Age of onset, substance use disorders, and percentage of patients in a manic episode or with psychotic features influences anxiety disorder comorbidity.